Alkaloids of narrow-leaved lupine as a factor determining alternative ways of the crop’s utilization and breeding - M. A. Vishnyakova; A. V. Kushnareva; T. V. Shelenga; G. P. Egorova (Вавиловский журнал генетики и селекции)
Narrow-leaved lupine (Lupinus angustifolius L.), a valuable leguminous crop adapted to a wide range of climatic conditions, has a very short history of domestication. For many centuries it was used mainly as a green manure, since the success and prospects of the multi-purpose use of the species depend on its breeding improvement, in particular, on a particular concentration of alkaloids in seeds and green mass. The first varieties of scientific breeding were created only in the 1930s after the appearance of low-alkaloid mutants. Despite wide prospects for use in various areas of the national economy, unstable productivity and susceptibility to diseases hinder the production of this crop. Obviously, breeders deal only with a small part of the gene pool of the species and limited genetic resources, using mainly low-alkaloid (sweet) genotypes to create new varieties. The genetic potential of the species can be used more efficiently. At the same time, it is rational to create highly alkaloid (bitter) varieties for green manure, while food and feed varieties should not lose their adaptive potential, in particular, resistance to pathogens, due to the elimination of alkaloids. In this regard, it seems to be a productive idea to create ‘bitter/sweet’ varieties combining a high content of alkaloids in the vegetative organs and low in seeds, which can be achieved by regulating the synthesis/transport of alkaloids in the plant. The paper discusses the current state of use of the species as a green manure, fodder, food plant. Information is given on the quantity and qualitative composition of narrow-leaved lupine alkaloids, their applied value, in particular, fungicidal, antibacterial, insecticidal, the use of lupine alkaloids as active principles of drugs. Along with promising breeding considerations, the possibility of using technologies for processing raw high-alkaloid materials with the accompanying extraction of valuable ingredients for pharmaceuticals is discussed. Information is briefly presented about the genomic resources of the species and the prospects for their use in marker-assistant selection and genome editing.